Understanding How Ideas are Linked in Compare and Contrast Essays: A Discourse Marker (DM) Study - Abidah, Khilda Husnia; Ratih, Elisa; Zen, Evynurul Laily; Lumbanbatu, Ira Maria Fran (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2024)
Discourse markers (DMs) are important when linking the first sentence and another sentence. The previous study showed that DMs can be varied in argumentative text of The Jakarta Post. However, some undergraduate students still face difficulties in using DMs, especially in academic writing, in the context of comparing and contrasting the essays, different from argumentative text. Therefore, this study aims to shed light on the various DMs employed by undergraduate students to establish logical transitions and also to find out the frequency of the DMs used within the context of compare and contrast essays. This study used qualitative methods to collect the data. The subjects of this study were 29 students majoring in English Literature from one of the state universities in Malang, East Java. To collect the data, the instruments used were the students' writing and AntConc 3.5.7 as the corpus analysis. The results were subsequently presented as percentages, offering valuable insights into the differences in DMs usage. The results showed that the students can demonstrate their ability to construct the compare and contrast paragraphs using the DMs properly. The findings contribute to the understanding of DMs usage in academic writing and provide practical implications for educators and learners seeking to improve their writing skills.